2018
DOI: 10.1055/s-0038-1676535
|View full text |Cite
|
Sign up to set email alerts
|

Can Platelet Mass Index Be a Parameter to Predict Intraventricular Hemorrhage in Very-Low-Birth-Weight Newborns?

Abstract: Objective Intraventricular hemorrhage (IVH) is an important problem in neonatal units not only in terms of its consequences but also its follow-up and the prediction of its emergence in newborns. In this study, we have compared platelet parameters such as platelet count (PC), mean platelet volume (MPV), and platelet mass index (PMI) in terms of IHV in very-low-birth-weight (VLBW) newborns. Thus, we have tried to determine platelet values to guide clinicians in both the prediction and follow-up of IVH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…On the other hand, Dani et al, also suggested that elevated MPV at 24 to 48 h of life was higher in BPD than in non-BPD groups, however, there was no significant difference of MPV between IVH and non-IVH groups (12). Korkmaz et al also suggested that platelet counts, MPV, and PMI at 12 h postpartum were not associated with IVH (26). In this study, PCT is an independent risk factor for IVH.…”
Section: Discussionmentioning
confidence: 41%
“…On the other hand, Dani et al, also suggested that elevated MPV at 24 to 48 h of life was higher in BPD than in non-BPD groups, however, there was no significant difference of MPV between IVH and non-IVH groups (12). Korkmaz et al also suggested that platelet counts, MPV, and PMI at 12 h postpartum were not associated with IVH (26). In this study, PCT is an independent risk factor for IVH.…”
Section: Discussionmentioning
confidence: 41%
“…Increased (> 13 fL) mean platelet volume (MPV) has been associated with hemorrhagic stroke, when compared to controls; nevertheless, neither MPV nor PLT were associated with outcome prognosis [16]. Platelet mass index (PMI), which is the product of PLT and MPV, has been proposed as predictor of intraventricular hemorrhage in very-low birth-weight newborns [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emerging evidence that platelets are contributing to the risk for ICH, their role remains partly understood. On the other hand, it is known that alterations of PLT and platelet indices including MPV, platelet distribution width (PDW), and platelet large cell ratio (P-LCR; the percentage of platelets with volume > 12 fL) are observed in platelet activation, consumption and replenishment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood indices related to platelets, which are indicators of inflammation in the neonatal period, have been evaluated in relation to neonatal and especially preterm morbidities. There are studies suggesting that there is an association between platelet-related markers including platelet mass index, mean platelet volume and IVH (11). Here, TLR was calculated in whole blood samples collected at the first hospitalization of preterm infants younger than 28 weeks, and the relationship between IVH was to be investigated.…”
Section: Introductionmentioning
confidence: 99%